Creating an environmentally responsible business: Evaluating, designing and prioritizing strategies - Febby Candra Pratama; Robertus Tang Herman (Faculty of Economics and Business, University of Muhammadiyah Malang, 2022)
Business organizations are constantly seeking ways to gain a competitive edge, and one approach is to develop effective strategies. To this end, this study aimed to identify internal and external factors that affect a company's performance and to formulate alternative strategies that could ensure its sustainability. The research focused on PT. Kastara Group Indonesia operates in the wholesale trade of coconut, coffee, and fish. To analyze the company's current position, the researchers employed Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal-External (IE) Matrix, SWOT Matrix, and Quantitative Strategic Planning Matrix (QSPM) in a case study. Based on the IE Matrix analysis results, the company requires a strategy for growth and development. The QSPM method was used to evaluate and compare alternative strategies. The results suggest that the company's strength lies in its ability to transform its business model digitally by creating dedicated platforms for wholesalers, which can reduce the length of the supply chain and expand the market.